The Role of Katuk Leaves in the Ration on Egg Production and Quality Laying Hens - D. T.R. Saragih (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2016)
Katuk (Sauropus androgynus (L) Merr) is belonged to the Family of Euphorbiacea. It is a herb plant with 2-3 m height. It is a tropical plant having many benefits for livestock productivity including for poultry production. The experiment was carried out according to completely randomized design. The number of cages used in this study was nine, in which the size of each cage was 1 m x 0.5 m. Three chickens were placed randomly in each cage. Once a week, the measurement for egg weight was conducted for the whole egg, including yolk weight, eggshell weight, yolk color intensity. All measured data were calculated for getting the average value. At the last week of the experiment (on the 55th week), samples were randomly taken from each treatment. The findings of research showed that adding 15% of katuk leaves meal into the laying ration resulted in positive effects on carcass and egg quality, indicated by an increase in egg yolk weight and vitamin A and a decrease in egg yolk cholesterol up to 16.82%. The content of estradiol hormone of the egg increased following the increase level of katuk leaves meal in the ration